Management of Uterine Leiomyoma - Sobia Nawaz Malik, Jehan Ara, Maliha Sadaf (Journal of Rawalpindi Medical College, 2012)
Background : To determine the prevalence of clinically significant myomas and review various treatment options of uterine leiomyomas. Methods: In this cross-sectional study patients admitted for abnormal uterine bleeding, due to fibroids, were included in the study. It included 54 premenopausal women, 30–50 years old, who had an intact uterus and were neither pregnant nor lactating, or using oral contraception or intra-uterine devices. Results: Uterine leiomyomata were detected in 54 women (22.4%) out of 240 patients admitted in the ward with abnormal uterine bleeding. Mean age for the women having leiomyoma was 39.3 years.Most women(18.4%) were multigravida. Surgical treatment was common treatment modality(70.3%) as compared to medical treatment(29.7%). Conclusion: Surgery continues to remain an important alternative when medical treatment fails to relieve symptoms of leiomyoma